M-commerce: development of ringtone purchasing system via SMS / Marhaini Abd Rashid - Abd Rashid, Marhaini (2004)
Nowadays, there are so many application created on m-commerce field, one of them is the application that allow user to buy a ringtone only using SMS technology. The main purpose of this research is to develop a ringtone purchasing system using SMS technology which is connected to infrared cable to detect mobile phone as a device in order to send input data to the system. Besides, this research tries to seek a different method that can use and easier in developing the system. Perhaps this research will give an awareness and guideline to developers in order to produce a high quality and robust product.